Utilization of organic and inorganic calcium and dehydrated food waste in improving egg production and egg quality of village chicken layers - Yusuf, Aliyu Ahmed (2016)
The study was conducted to investigate the performance of different organic and inorganic dietary calcium from halal sources in Malaysian village chicken layers diet and utilization of dehydrated food waste (DFW) as an economical alternative feed supplement in Malaysian village chicken layers for better egg production and quality. One hundred and twenty (120) Malaysian Village chickens (Arabian strain) at the age of 50 weeks old were randomly assigned to four dietary feed treatments with different calcium and energy sources. Commercial layers feed was used as control diet (T1). Formulated layer feed ingredients + DFW + Bone meal as a source of dietary calcium (T2). Formulated layer feed ingredients + DFW + Eggshell powder as a source of dietary calcium (T3). Formulated layer feed ingredients + DFW + Limestone as a source of dietary calcium (T4). Each treatment was replicated 3 times with 10 birds per replicate. Restaurant food leftover (mainly rice) was locally sourced from 15 different halal restaurant within Universiti Putra Malaysia (UPM) and processed to dehydrated food waste (DFW) and used as energy sources in T2, T3, and T4. Raw tibia bovine bone from Malaysian Brakmas breed of cattle was source from meat processing plant of the Department of Animal Science, UPM and processed to bone meal as source of organic dicalcium phosphate (DCP) (Ca + PO4) in T2. Eggshell waste was source from hatcheries of poultry research unit of Ladang two, UPM and processed to eggshell powder for organic source of CaCO3 (calcium carbonate) in T3. Limestone powder was purchased from animal feeds supplier (Animal feed vendor) and used as inorganic mineral source of calcium carbonate (CaCO3). The feeding period lasted for 7 weeks in which feed were measured every day and the leftover also measured the following morning (24 hours) for daily feed intake. Clean and fresh water was given ad libitum every morning. The effects of different dietary calcium sources and DFW on production and egg quality traits (feed intake, body weight gain, egg production, feed conversion ratio, egg weight, egg height, egg width, egg volume, eggshell weight, eggshell thickness, eggshell percentages, albumen weight, albumen height, albumen percentage, yolk weight, yolk percentage, yolk colour, egg grade and haugh units) were evaluated. All data obtained in 3rd, 5th, and 7th weeks on egg quality traits were subjected to one way ANOVA, except that of egg production where all data’s for the 7 weeks were used. Statistical test was performed and means comparism between performance of experimental dietary feed treatments on production and egg quality were done using Duncan multiple range test at P˂ 0.05. The results indicated that, treatments had statistical (P<0.05) significant effects on egg quality traits, except in feed intake, body weight gained, FCR and weekly rate of lay. The result showed that, T2 was highly utilized for production of eggs with superior qualities on egg weight (49.71g), egg height (53.13mm), egg width (41.40mm), egg volume (47.67ml), eggshell weight (5.67g), eggshell thickness (0.34mm), albumen weight (26.70g), albumen height (3.63mm) yolk weight (16.77g), yolk percentage (33.90%), and yolk colour (4.25 points) over other dietary feed treatments. Based on the outcome of this result, it can be concluded that, organic DCP from bovine bone meal and DFW from restaurant leftover are promising poultry feedstuff for better nutrition, production of quality eggs and provision of halal feed ingredients for poultry production. Also, the result proves the hypothesis that absorption of calcium from organic source is better than absorption from inorganic sources. Therefore, organic DCP from bovine bone meal and DFW can be offered to small-scale farmers as an economical substitute to conventional feedstuff and halal poultry feed ingredients which may help to contribute effectively on production of quality eggs that will provide adequate protein to population from village chicken layers.